2017
DOI: 10.1007/s10803-017-3082-8
|View full text |Cite
|
Sign up to set email alerts
|

Language ENvironment Analysis (LENA) in Phelan-McDermid Syndrome: Validity and Suggestions for Use in Minimally Verbal Children with Autism Spectrum Disorder

Abstract: Phelan-McDermid syndrome (PMS) is a single-locus cause of developmental delay, autism spectrum disorder, and minimal verbal abilities. There is an urgent need to identify objective outcome measures of expressive language for use in this and other minimally verbal populations. One potential tool is an automated language processor called Language ENvironment Analysis (LENA). LENA was used to obtain over 542 h of audio in 18 children with PMS. LENA performance was adequate in a subset of children with PMS, specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 48 publications
4
32
1
Order By: Relevance
“…In particular, LENA accuracy (against human transcribers) was negatively correlated with child chronological age, with the authors suggesting that acoustic changes in the voices of older children leading to increasing incidences of LENA misclassifying as adult vocalizations. Consistent with Dykstra et al [], Rankine et al [] suggested that high levels of echolalia and repetitive speech may confound interpretation of the data, with the quantity and quality of vocalizations not necessarily correlated. To illustrate, it is possible that two children––one with relatively mild ASD characteristics displaying frequent directed and flexible communication and another with severe intellectual disability and high rates of echolalia and repetitive speech may present with a similar rate of CVs as measured using LENA (i.e., quantity of vocalizations), despite a fundamental difference in the quality of their vocalizations.…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…In particular, LENA accuracy (against human transcribers) was negatively correlated with child chronological age, with the authors suggesting that acoustic changes in the voices of older children leading to increasing incidences of LENA misclassifying as adult vocalizations. Consistent with Dykstra et al [], Rankine et al [] suggested that high levels of echolalia and repetitive speech may confound interpretation of the data, with the quantity and quality of vocalizations not necessarily correlated. To illustrate, it is possible that two children––one with relatively mild ASD characteristics displaying frequent directed and flexible communication and another with severe intellectual disability and high rates of echolalia and repetitive speech may present with a similar rate of CVs as measured using LENA (i.e., quantity of vocalizations), despite a fundamental difference in the quality of their vocalizations.…”
Section: Introductionsupporting
confidence: 64%
“…Rankine et al [] examined the validity and reliability of LENA variables against transcribed samples and standardized measures, for a group of 18 minimally verbal children (i.e., not using phrase speech) with Phelan‐McDermid Syndrome (commonly associated with ASD), aged 30–172 months. Each participant completed between one and three whole day recordings (maximum 16 hr) across home, education, and clinical settings.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations